Adaptation to Temporal Shocks: Influences of Strategic Interpretation and Spatial Distance. (10th October 2013) - Pérez‐Nordtvedt, Liliana; Khavul, Susanna; Harrison, David A.; McGee, Jeffrey E.
Abstract Even when shocks in a firm's environment are predictable, their consequences are not. Using the relocation of the Dallas Cowboys Stadium as a rich case of such a disruption, we investigate how combinations of strategic interpretation and spatial distance influence incumbent business owners' decisions to pursue temporal adaptation as a response. Temporal adaptation (TA) comprises timing rather than content changes by the firm seeking to adjust to the reconfigured environment. Survey data from 168 business owners show that strategic interpretation directly influences TA decisions. However, the effect of strategic interpretation on the TA decision is moderated by the spatial (geographic) distance of the incumbent firm from the locus of the disruption. Furthermore, results suggest that through strategic interpretation, spatial distance also indirectly affects the business owners' decisions to make temporal changes. Data collected 1.5 and 4 years later suggest that TA responses are related to performance and may be indicative of a particular type of TA, organizational entrainment (OE), which concerns the synchronization of organizational activity cycles with cycles in the environment.